Perencanaan Produksi Agregat untuk Optimalisasi Biaya: Studi Kasus Van'z Collection, Produsen Garmen Skala Kecil - Zahra Nur Afifah; Ayi Tejaningrum (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study aims to evaluate the aggregate production planning system and explore alternative aggregate strategies to improve cost efficiency in the production planning process. The primary objective of aggregate planning is to mitigate unpredictable fluctuations, such as those caused by seasonal or external factors, and to minimize total planning costs. The research focuses on small and medium-sized enterprises (SMEs) operating in the garment manufacturing sector in Bandung, West Java. The methodological approach includes a case study design, data analysis, and demand forecasting using QM for Windows with forecasting techniques such as Moving Average and Exponential Smoothing. Microsoft Excel is utilized to simulate and analyze various aggregate planning strategies. This study examines three key strategies: subcontracting, labor adjustment, and working hour regulation. Each strategy incurs distinct cost components, subcontracting costs, recruitment and termination costs, and overtime costs, respectively. Field analysis reveals that subcontracting is the most cost-effective strategy. Its advantages include the ability to engage other SMEs in meeting demand, low risk of delivery delays, and reduced exposure to raw material shortages and processing time constraints. However, it carries a risk of quality variation. Therefore, it is recommended that firms implementing a subcontracting strategy maintain strict quality control to ensure compliance with product specifications.